Good fiction guide - edited by Jane Rogers; consultant editor; Hermione Lee; assistant editors; Mike Harris; Douglas Houston (Oxford University Press, 2001)
The entries provide a flavor of each writer's work, recommend which of their books to read, and include suggestions for related reading, leading you to other writers whose work may be either comparable or an interesting contrast. Equally important, the guide includes 34 essays that illuminate genres such as Crime, Adventure, Romance, and Magic Realism, or offer intriguing looks at the national literatures of such places as Australia, India, and the Caribbean. Each entry is a personal essay by an expert in the field and includes their top twelve recommended titles